Critical Factors Affecting Trust in the Wine Supply Chain in Greece: A Grey DEMATEL Approach - Eleni-Efthymia Psychogiou; Giannis T. Tsoulfas (Logistics)
Background: Although trust is a well-studied topic in supply chain management, the case of the wine supply chain has not been adequately investigated. Methods: A hybrid approach combining qualitative and quantitative data analysis was adopted. The research was divided into two phases: (i) identification of critical factors based on the literature, and (ii) analysis of eight experts’ insights on those factors by employing the grey DEMATEL approach. Results: Fourteen factors that affect trust in the wine supply chain were identified based on the academic literature. From the analysis of the experts’ views, with the use of the grey DEMATEL approach, the factors were classified into two groups. The first group (nine factors) concerns the factors that affect the rest and the second group (five factors) concerns those which are affected by the former factors. Conclusions: The study of trust in the supply chain can be further improved by monitoring the trends in the sector and by engaging a wider audience of stakeholders. This approach can be applied to various regions in order to examine whether the situation is different from country to country. Stakeholders will have the necessary information to support their decisions and prioritize their objectives, aiming at improving the whole supply chain.